2020
DOI: 10.1111/jan.14296
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide prevalence of sexual harassment towards nurses: A comprehensive meta‐analysis of observational studies

Abstract: Aims Sexual harassment towards nurses is a major concern universally, but no meta‐analysis on the worldwide prevalence of sexual harassment towards nurses has yet been published. This study examined the worldwide prevalence of sexual harassment against nurses and explored its moderating factors. Design Meta‐analysis of observational studies. Data sources The PubMed, PsycINFO, EMBASE, and Web of Science databases from their commencement date to February 2018 were systematically and independently searched by two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 67 publications
2
58
1
2
Order By: Relevance
“…Sexual harassment against nurses and midwives has emerged as a significant issue [28]. A meta-analysis of the worldwide prevalence of sexual harassment towards nurses (n = 52,345 participants) reported that the prevalence of sexual harassment towards nurses during their nursing career was 53% and 13% in the preceding 12 months [29].…”
Section: Physical Violencementioning
confidence: 99%
“…Sexual harassment against nurses and midwives has emerged as a significant issue [28]. A meta-analysis of the worldwide prevalence of sexual harassment towards nurses (n = 52,345 participants) reported that the prevalence of sexual harassment towards nurses during their nursing career was 53% and 13% in the preceding 12 months [29].…”
Section: Physical Violencementioning
confidence: 99%
“…However, this may also have to do with under-reporting of sexual harassment by females due to reasons, such as shame and embarrassment. 28 There was also wide variation by the type of measurement approach (direct query vs behavioural acts or categories). Studies were able to capture a higher prevalence for certain individual behaviours or acts, such as suggestive comments, inappropriate staring, unwanted touching and sexual calls, than with only a direct question asking if they have been sexually harassed.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, during the full-text screening, we excluded studies on healthcare professionals (eg, nurses and doctors) as this population was well studied with two meta-analyses focused exclusively on this group in China 26 27 and one on nurses globally. 28 The final set of included full-text articles was formally appraised by two reviewers (MR and HS). Data from full-text sources were extracted using the following headings: first author and year; country; study setting; description of study sample; study design and sample number; information provided on sexual harassment-study definition, measurement approach, reporting period, prevalence estimates, frequency of acts and main perpetrator; outcomes (eg, sleep disorders or mental health effects, if measured), outcome direction and nature of effect.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…For example, 12.9% of the nurses according to the results of a study on the subject 8 and 28% of the nurses according to the results of a meta-analysis study were observed to have come across this behavior. 9 According to the results of the meta-analysis conducted by Lu et al, 19 53.4% of the nurses encountered this behavior during their careers. In a study conducted in Turkey, this rate was 71.7% 20 .…”
Section: Epidemiology Of Isbmentioning
confidence: 99%